Pengembangan Kompetensi Dosen melalui Sosialisasi Penyusunan Rencana Pembelajaran Semester (RPS) Era Revolusi Industri 4.0 - Muslim Muslim; Dedi Setiawan; Hendra Dani Saputra (Universitas Mathla'ul Anwar Banten, 2021)
DEVELOPMENT OF LECTURERS COMPETENCIES THROUGH THE SOCIALIZATION OF THE SEMESTER LEARNING PLAN (RPS) ERA OF INDUSTRIAL REVOLUTION 4.0. This socialization activity is an activity carried out in the Automotive Engineering Department, Faculty of Engineering, Padang State University. This service activity is to increase the knowledge and skills of lecturers in compiling RPS in accordance with the demands of the world today. This is to make it easier for lecturers to plan, compile RPS and evaluate learning oriented in the 4.0 revolution era. This activity was attended by 24 lecturers majoring in automotive engineering. In this socialization activity, it was explained how to prepare RPS in the era of the industrial revolution 4.0 and also to develop lecturer competence because making RPS is the obligation of lecturers in preparing for the learning process later. The data shows a lack of interest from lecturers in compiling and developing RPS. There are also data results that show the lack of student motivation in learning activities which is part of the readiness of the lecturers themselves in completing learning tools. The method used is science and technology substitution by offering a new, more modern science and technology than the old one. The final result is that the overall service activity process has been considered quite good and useful for automotive engineering majors and is important to be developed as part of the completeness of learning tools.